PERENCANAAN PEMBANGUNAN PARTISIPATIF GUNA MEWUJUDKAN ASPIRASI MASYARAKAT DI BADAN PERENCANAAN PEMBANGUNAN DAERAH KABUPATEN MUSI BANYUASIN - Ridwan Ridwan; Juwandi Panab (Jurnal Pallangga Praja (JPP), 2022)
development that prospers the community is development that is universal in all sectors of the social life ofsociety. To achieve development goals, massive and intensive cooperation and collaboration between the government and the community is needed. Creative and intensive collaboration carried out in Musi Banyuasin Regency by conducting development Planning Consultations or Musrembang. Musrembang is a policy-makingprocess involving active community participation in channeling their aspirations. This research was conductedto identify community participation in policy making and the inhibiting and supporting factors of communityparticipation. This research was conducted using a qualitative method with a descriptive approach that describes the state of community participation in development. This study uses data analysis using participatorydevelopment planning theory by McGee which includes the following dimensions: actors (People), Knowledge(Knowledge) and spaces (space). Based on the results of the research, to build community participation in development the Government has assigned sub-districts and villages to immediately prepare the implementationof the annual musrenbang and immediately socialize it to the community. The program has been running well,but there are obstacles in the form of funding in the process of organizing activities.